The Role of Al-Hukm in Shaping Islamics Business Behaviour - Delima Sari Lubis; Aliman Syahuri Zein; Erlina Yulianda; Ira Sumarni (Journal of Islamic Economics and Finance Studies, 2025)
The integral relationship between Al-Hukm and Islamic business behavior, which will have an impact on society and the surrounding environment. Legal principles in Islam function as a moral foundation in business practices. These principles guide business actors to make decisions that reflect Islamic values, namely honesty, transparency and social responsibility. This framework encourages businesses to not only achieve financial success now, but also consider future impacts. Through Islamic business ethics, Al-Hukm will shape business behavior that is not only in line with Islamic values ​​but also encourages economic development. This research is a qualitative-descriptive type of research The data collection method used is documentary study, namely a method related to various existing documents about the research object. The emphasis on business ethics as part of Al-Hukm has a positive impact on the sustainability of Islamic business. Honesty, transparency and social responsibility are an inseparable part of business practices inspired by Al-Hukm principles. This is what distinguishes Islamic business as a deep ethical force Overall, Al-Hukm's role is not only limited to regulation and compliance, but forms the essence of responsible and ethical Islamic business behavior. By understanding and respecting the principles of Al-Hukm, Islamic business becomes a transformational force that not only creates economic value but also contributes to the development of a better society. Thus, the role of Al-Hukm is not only normative but also formative in shaping the character of an empowered and ethical Islamic business.